Kompetensi Mahkamah Syari’ah Dalam Menangani Perkara Ekonomi Syari’ah - Nazaruddin Nazaruddin (Ma'had Aly Raudhatul Ma'arif, 2023)
This article aims to investigate the competence of the Religious Courts in handling Islamic Economic cases. A significant change that recently occurred is the expansion of the Religious Court's jurisdiction in accordance with Law No. 3 of 2006, particularly concerning the handling of Islamic Economic cases in Indonesia. The Religious Courts are now authorized to handle cases related to Islamic financial services, including Islamic banking disputes. This amendment not only broadens the authority of the Religious Courts but also provides a clear scope for Islamic economic disputes. The scope extends beyond banking issues to include Islamic microfinance institutions, Islamic insurance, reinsurance, Islamic mutual funds, Islamic bonds, medium-term Islamic securities, Islamic securities, Islamic multifinance, Islamic pawnshops, and other Islamic financial institutions and businesses.